An application of the Black–Litterman model using exponential GARCH-in-mean model - Nyman, Elsa (My University, 2019)
The Black–Litterman model is an alternative asset allocation method that was developed to challenge the modern portfolio theory in the international asset allocation decision-making context. The modern portfolio theory takes only the mean and the variance of the asset returns into account and therefore it is called “mean-variance optimization”. There are several issues related to this model and the Black–Litterman model was developed to overcome these issues. The main contribution of the model is that it incorporates investors’ subjective views to the model which the modern portfolio does not take into consideration. This study applies exponential GARCH-in-mean model (EGARCH-M) to estimate proxies for the investors’ views in the Black–Litterman model. EGARCH-M model was chosen as it takes many statistical properties of asset returns into consideration. The study is conducted for a theoretical portfolio consisting of twelve MSCI country indices from different economic backgrounds. The theoretical investors’ views are built based on the results of EGARCH-M and the new revised vector of expected returns is computed using these inputs and the prior distribution of implied equilibrium returns and historical variance-covariance matrix. Finally the new weights are calculated and compared to the benchmark portfolio based on naïve allocation.

Black–Litterman -malli on sijoitusten allokointimalli, joka kehitettiin haastamaan moderni portfolioteoria globaaleissa sijoitusten allokointipäätöksissä. Moderni portfolioteoria keskittyy ainoastaan sijoituskohteiden keskiarvoon (mean) ja varianssiin (variance), joten sitä kutsutaan myös ns.mean-variance -optimoinniksi. Kyseiseen malliin liittyy useita ongelmia, jotka Black–Litterman malli pyrkii huomioimaan. Black–Litterman -mallin tärkein hyöty on se, että se ottaa huomioon sijoittajien subjektiiviset näkemykset. Tässä tutkielmassa sovelletaan eksponentiaalista GARCH-in-mean -mallia (EGARCH-M) ja estimoidaan proxy -muuttujat sijoittajien näkemyksille Black–Litterman malliin. EGARCH-M - malli soveltuu tähän, sillä se ottaa useita tuottojen tilastollisia ominaisuuksia huomioon. Tässä tutkielmassa sovelletaan mallia indeksituottojen aikasarjadatalle käyttäen MSCI maaindeksejä erilaisista taloudellisista lähtökohdista. EGARCH – mallin tuloksista muodostetaan teoreettiset sijoittajien näkemykset ja Black–Litterman -mallin mukaiset tuotot lasketaan käyttäen näitä näkemyksiä sekä CAPM -malliin perustuvia tuottoja ja varianssi-kovarianssi matriisia. Lopuksi lasketaan uudet Black–Litterman -mallin mukaiset painot sijoituskohteille ja verrataan valittuun benchmarkiin, joka tässä tapauksessa on ns. naïve allocation eli sijoituskohteiden painot jaetaan tasaisesti portfoliossa.
Keywords: asset allocation, portfolio theory, CAPM, the Black–Litterman model, GARCH